Evaluation of the Overview of Pharmaceutical Service Activities at Meranti Pharmacy, Jambi City, by the Minister of Health Regulation - Diky Okta Yudha Putra (CV Projurnal Mitra Publikasi, 2025)
The internship activities were conducted at Meranti Pharmacy for one month to review and perform pharmaceutical services according to the Regulation of the Minister of Health of the Republic of Indonesia No. 73 of 2016, which aims to improve the quality of patient life. This regulation served as the foundation for comparing standard provisions with the actual pharmaceutical services provided at Meranti Pharmacy. The evaluation encompassed two main areas: managerial activities and clinical pharmacy services. Managerial activities included the management of pharmaceutical preparations, medical devices, and consumable materials, covering aspects such as planning, procurement, receipt, storage, destruction, control, recording, and reporting. Clinical pharmacy services involved prescription review, dispensing, Drug Information Services (DIS), and monitoring of adverse drug reactions (ADR). The findings indicate that Meranti Pharmacy demonstrated strong compliance with pharmaceutical service standards, particularly in providing patient counseling across regulated categories, including patients with special conditions, long-term therapy/chronic diseases, use of drugs with special instructions, narrow therapeutic index, polypharmacy, and low adherence levels. The study concludes that the Managerial and Pharmaceutical Service System at Meranti Pharmacy aligns with the Minister of Health Regulation Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies.